Optimalisasi Peran Tenaga Kerja Rumah Sakit dalam Mewujudkan Rumah Sakit Unggul Berbasis Pelayanan Berkualitas - Febriantie, Nadya; Ardan, M. (LPPM Institut Pendidikan Nusantara Global, 2025)
Hospitals are one of the healthcare facilities that play an important role in providing services to the community through various interacting disciplines. The main objective of this activity is to analyze the effectiveness of hospital administrative management and to identify operational issues that affect the quality of services. The community service activity was conducted at UPTD RSUD Kelas D Pratama Sendawar from September 1 to September 30, 2025. Based on the results of observations, interviews, and situational analysis, it was found that the shortage of administrative staff is the main issue that directly impacts service efficiency. The limited number of administrative employees forces staff from other units to take on multiple roles, resulting in excessive workloads, service delays, and reduced coordination effectiveness between units. The analysis using the fishbone method indicated that the root causes of the problem are related to human resource factors, regional policies, limited budgets, and obstacles in the recruitment process for civil servants (ASN) and contract workers. Alternative solutions were analyzed using the Reinke Method, and the main recommendation was to conduct workload evaluations and implement a more proportional redistribution of tasks. Medium-term recommendations include proposing new ASN positions and recruiting contract workers (TKK) through the BLUD mechanism. This community service activity emphasizes that optimizing the role of administrative personnel plays a crucial part in realizing high-quality and competitive hospital services.